The Relationship of Pregnant Woman who Consume Betel Nut to Periodontal Disease Which will Affect Pregnancy Outcome - Christina Ngadilah; Applonia Leu Obi; Melkisedek O. Nubatons (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Several studies have found that areca nut increases gingival inflammation, inhibits immune reactions, affects osteoblasts, and may be cytotoxic to periodontal fibroblasts. Pregnant women who consume betel nut, the assumption is that it will worsen the condition of periodontal tissue so that it will affect the condition of pregnancy outcome, including low birth weight. Analyzing the influence of pregnant women who consume betel nut on the condition of the periodontal tissue that will affect pregnancy outcome. Using a cross sectional analysis to analyze the effect of consuming betel nut on periodontal tissue damage that will cause bad pregnancy outcomes by accidental sampling in pregnant women aged between 17-50 years at the Lelogama Health Center, South Amfoang, Kupang Regency. There is a relationship between consuming betel nut and the severity of periodontal tissue, P < 0.05, where there is a strong correlation of 48.3%. Mothers consumed betel nut whose gums 69% in poor periodontal condition. About 6.2% of mothers knew that betel nut affects pregnancy outcome, the remaining abou 93.8 dont understand. The large number of mothers who consume betel nut with poor periodontal tissue conditions, it is feared that disturbances in pregnancy outcomes such as low birth weight and stunting can occur.